(untitled) (Journal of International Studies, 2015)
The aim of this study is to examine Nigeria’s hegemony in West Africa and its implications on Nigeria’s national core development programmes. This is done via critical examination of some selected regional and national development indicators with a view to fi nd ways of improving the overall national performance as signifi cant contribution to regional development. On political impact, the study found that successive Nigerian governments were engrossed in unprecedented national corruption than development, diverting billions of dollars meant for national development in the guise of national security, regional peacekeeping, humanitarian intervention and socio-economic development of the sub region. The consequences of such political ineptitude were widespread: failed leadership, clientelism, rentierism, political apathy, escalating national insecurity, wide-spread poverty and unemployment and poor macroeconomic development. Overall, the study opines that Nigeria should shore up greater commitment and responsibility towards her national and human capital development, massively improve the infrastructure, reorientate both military and political elites to ensure integral national growth, overhaul her regional and foreign policy goals to meet her national interest goals as true catalyst for regional development.